104 ADAPTATIONS IN EXCITATION-CONTRACTION COUPLING IN CARDIAC-SPECIFIC NA+/CA2+ EXCHANGER KNOCKOUT MICE. (1st January 2005) - Pott, C.; Philipson, K. D.; Goldhaber, J. I.
Abstract : The Na+/Ca2+-exchanger (NCX1) is regarded to be the main Ca2+ extrusion mechanism of the cardiomyocyte. We have recently introduced a murine model with a cardiac-specific knockout (KO) of NCX1 that is viable to adulthood and does not exhibit compensatory changes in protein expression levels (Henderson et al., 2004). In the present study, we have used the patch clamp technique and the fluorescent Ca2+ indicator fura-2 to characterize adaptations of excitation-contraction (E-C) coupling in isolated adult ventricular myocytes from these KO mice. Resting Ca2+ concentration (WT: 109621 nM; KO: 81613 nM) and caffeine-induced Ca2+ transients (a measure of SR Ca2+ load; WT: 583676 nM; KO: 584635 nM) did not differ between KO (n=9) and WT (n=9; p=N.S.). To measure Ca2+ extrusion capability of the cells in the absence of SR Ca2+ uptake, we applied caffeine (5 mM) for 8s while monitoring the Ca2+ transient. In WT cells, the caffeine-induced Ca2+ transient was decreased to 50% of its peak within 2.460.4s (n=11). In KO myocytes, [Ca2+] decreased by only 1965% after the full 8s of caffeine (n=11), similar to WT in the presence of 10 mM Ni+ to block NCX activity (n=4). In WT but not KO cells, rapid removal of bath Na+ (1s) and depolarization of cells to +80 mV (1s) induced Ca2+ entry via reverse Na+/Ca2+ exchange (n=5). Peak L-type Ca2+ current (ICa) during voltage clamps from 230 to 40mV was decreased in KO myocytes (4.060.4 pA/pF; n=4) as compared to WT (9.661.5 pA/pF; n=7; p≤0.05). Despite the different ICa the corresponding Ca2+ transient amplitude was similar (KO: 456668 nM; WT: 518673 nM; p≥0.05), yielding an increase in the gain of E-C coupling in KO (115611 nM/(pA/pF)) as compared to WT (4765 nM/(pA/pF); p≤0.001). These findings suggest that there is no compensatory alternative Ca2+ extrusion mechanism in NCX1 KO myocytes. Rather, Ca2+ influx is limited by a decrease in ICa and contractility is maintained by an increased E-C coupling gain.